The Relationship Between Family Support And Compliance Of Plha With Antiretroviral At RSU HKBP Balige - Elfrida Nainggolan; Almina Rospitaria Tarigan (CV. AFDIFAL MAJU BERKAH, 2023)
The purpose of this study was to find out the relationship between family support and compliance with PLWHA taking antiretrovirals at HKBP Balige General Hospital. The research design used a correlative descriptive study using a cross sectional design. This research was conducted at RSU HKBP Balige, the study population was all ODHA families who were treated at the outpatient polyclinic at RSU HKBP Balige, 32 people. The sample selection method uses the n total sampling method, which is a sampling technique where the number of samples is equal to the population. The analysis used was univariate and bivariate tests. Based on the results of the analysis using the Chi Square statistical test with the SPSS version 16.0 program, it was found that ρ value = 0.016 <α = 0.05, meaning that Ho was rejected and H1 was accepted